Forecast combination and Bayesian model averaging: A prior sensitivity analysis - Martin Feldkircher (University of Salzburg, Department of Social Sciences and Economics, 2010)
In this study we evaluate the forecast performance of model averaged forecasts based on the predictive likelihood carrying out a prior sensitivity analysis regarding Zellner's g prior. The main results are fourfold: First the predictive likelihood does always better than the traditionally employed 'marginal' likelihood in settings where the true model is not part of the model space. Secondly, forecast accuracy as measured by the root mean square error (rmse) is maximized for the median probability model. On the other hand, model averaging excels in predicting direction of changes. Lastly, g should be set according to Laud and Ibrahim (1995) with a hold-out sample size of 25% to minimize the rmse (median model) and 75% to optimize direction of change forecasts (model averaging). We finally apply the aforementioned recommendations to forecast the monthly industrial production output of six countries beating for almost all countries the AR (1) benchmark model.
Keywords: C11; C15; C53; 330; Forecast combination; Bayesian model averaging; median probability model; predictive likelihood; industrial production; model uncertainty